Between the 3rd and 2nd millennia BC : exploring cultural diversity and change in late prehistoric communities - Lopes, Susana Soares,; Gomes, Sérgio Alexandre, (Archaeopress archaeology., 2021)
This collection of studies on the cultural reconfigurations that occurred in western Europe between the 3rd and 2nd millennium BCE focuses on the evidence from the West of the Iberian Peninsula, and one on the South of England. They explore regional diversity and challenge grand narratives regarding Chalcolithic and Bronze Age communities.